Changing the culture of social care in Scotland: Has a shift to personalization brought about transformative change?. (8th November 2017) - Pearson, Charlotte; Watson, Nicholas; Manji, Kainde
Abstract: In April 2014, the Social Care (Self‐directed Support) (Scotland) Act 2013 (SDS Act) was implemented in Scotland. This marked a major shift in how social care is delivered and organized for both users and professionals across the country. Whilst it emerged through the personalization agenda—which has dominated international social care systems over recent years—self‐directed support (SDS) represented a significant shift in thinking for service provision in Scotland. In this article, we review the initial stages of policy implementation. Drawing on two Freedom of Information requests from 2015 and 2016 and a series of interviews with local authority practitioners, we argue that, to date, SDS has yet to produce radical transformative change. We explore the reasons behind this through four key themes. First, we highlight the challenges of promoting the principles of co‐production in policy and suggest that, in reality, this has been compromised through SDS implementation. Second, we suggest that SDS has been caught up in a policy overload and ultimately overshadowed by new legislation for health and social care integration. In looking at the impact of this relationship, our third theme questions the role of new partnership working. Lastly, we argue that the timing of SDS in a period of acute austerity in social care has resulted in disabled people being offered limited choice rather than increased opportunities for independent living.